LAW ENFORCEMENT AGAINST NARCOTICS DISTRIBUTION THROUGH VAPE LIQUID: A STUDY AT THE NORTH SUMATRA REGIONAL POLICE - Auro Dasanov; M. Citra Ramadhan; Andi Hakim Lubis (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research is entitled Law Enforcement Against the Spread of Narcotics Through Vape Liquid (North Sumatra Regional Police Study). The formulation of the problem is (1) What are the factors that cause the spread of narcotics through vape liquid? (2) How is law enforcement carried out by the North Sumatra Regional Police in overcoming the spread of narcotics through vape liquid? (3) What are the obstacles for the North Sumatra Regional Police in enforcing the law against the spread of narcotics through vape liquid? The research method used is normative juridical legal research, with a descriptive analytical research type. To approach the problem, a normative juridical approach is used. The data used are primary and secondary data. The results of the study show that (1) The unemployment factor has a significant impact on perpetrators in carrying out their actions to distribute narcotics through vape liquid. Of course, this is the main source of narcotics dealers to get money even though it is done in an improper way to support their family's needs (2) Law enforcement carried out by the North Sumatra Regional Police in overcoming the spread of narcotics through vape liquid is to ensnare narcotics perpetrators with Article 114 subsidiary Article 112 of Law No. 35 of 2009 with a penalty of 20 years in prison. After an investigation at the Police level, the North Sumatra Regional Police have then submitted the case files to the Medan District Attorney's Office to be processed in court to obtain legal certainty. (3) Obstacles to the North Sumatra Regional Police in enforcing the law on the spread of narcotics through vape liquid, namely the increasing spread of cases of abuse of electronic cigarettes which contain narcotics, this is because Indonesia does not yet have specific regulations governing alternative tobacco products, other than those related to excise. These regulations must be separated from the Narcotics Law or the Narcotics Law must be immediately revised with the addition of liquid narcotics.